The Forgotten Labour of Craft: Exploitation and Organizing in Artisanal Industries - Anderson, Benjamin (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2021)
Over the last decade, firms positioning themselves as craft or artisanal have proliferated in the urban environments of the Global North. Selling themselves as community hubs, friendly neighbours, anticorporate crusaders, and environmental stewards, craft industries – craft breweries, artisanal bakeries, heritage clothing manufacturers, and the like – have effectively insulated themselves from critique. Hidden beneath this veneer, however, are the accounts of countless workers detailing experiences of harassment, overwork, low pay, and discrimination. Motivated by the methodological orientation of workers’ inquiry, this article recounts attitudes and experiences offered by craftworkers and craftspeople about their working conditions, motivations, and attempts to organize in craft industries, particularly craft brewing. Worker testimony reveals a profound disconnect between the optimistic industrial mythologies offered up by craft discourse and the rigid hierarchies, unequal division of labour, and toxic cultures many observed in their workplaces. Contrary to the pervasive artisanal allure that motivates many workers to seek out work in craft brewing and similar industries, the research presented here also suggests new levels of working-class consciousness and solidarity emerging in these industries and profiles attempts by craft brewery workers to organize their workplaces and fight to improve conditions.